ETR 300 : Adzhim Le Jewels / Siti Faezah Isa ... [et al.] - Isa, Siti Faezah; Abdul Kadir, Lina Hariza; Mansor, Marwanis; Sudirman, Suria Sukma Wirdaningseh (2020)
Adzhim Le Jewels is a business which provide manufacturing, selling, buying and customizing jewellery services. Products are only based on gold. We have our own concept which will make our business attract more customers, and will evolve in the future. Our business's main element are gold and gems. A variety of jewellery will be provided based on the customers taste.